Aquatic Insects of Man-Made Habitats: Environmental Factors Determining the Distribution of Caddisflies (Trichoptera), Dragonflies (Odonata), and Beetles (Coleoptera) in Acidic Peat Pools. Issue 1 (8th February 2019) - Buczyńska, Edyta; Buczyński, Paweł
Abstract: As degradation of sensitive habitats like Sphagnum L. (Sphagnales: Sphagnaceae) peatbogs is endangering their invertebrate fauna, artificial peat pools may offer peatbog insect fauna a chance of survival. The entomofauna of seven peat pools in a peatbog and its surrounding natural marginal zone in SE Poland was investigated at the level of species, assemblages and faunistic metrics, indicating the key environmental drivers of the insect distribution and their implications for the biodiversity and potential conservation of these habitats. The species composition, specialists, and insect assemblages of the peat pools were linked with the fauna typical of both peatbogs and dystrophic pools with an open water surface. The most specialized fauna was found in the pools with the largest Sphagnum cover: only tyrphobionts, of all the ecological elements, significantly discriminated the fauna of peat pools and the marginal zone. Sphagnum cover was the key structural factor affecting the distribution of all the insects. Additionally, dragonflies were dependent on pH, beetles on temperature, and caddisflies on dissolved oxygen; however, structural factors—apart from Sphagnum cover—pool perimeter and emergent vegetation cover were predominant. Our results show that appropriate management of the structural factors of peat pools, especially Sphagnum cover, and the provision of different successional stages, can enhance biodiversity and help to maintain a valuable specialist fauna. Even along small environmental gradients and in a homogeneous area, the response of insects is highly differentiated. Dragonflies probably best represent the conservation value of the overall invertebrate fauna of Sphagnum bogs.